2019
DOI: 10.30802/aalas-jaalas-18-000092
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue, Euthanasia Stress, and Their Management in Laboratory Animal Research

Abstract: Many people in diverse roles contribute to the success of animal welfare and research outcomes in laboratory animal research programs. These personnel include but are not limited to animal care and veterinary staff, researchers and their teams, facility management support, IACUC and compliance members, institutional officials, board members, vendors, security personnel, administrative staff, and all others involved in laboratory animal science programs. Any of these persons are potentially vulnerable to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 13 publications
2
36
0
1
Order By: Relevance
“…Similarly, an inability for those working in research animal facilities to speak openly about their questions and concerns related to animals or research, because of a lack of workplace openness, can lead to workplace stress ( 3 , 27 ). In human health care fields such as nursing, a perceived lack of opportunity to discuss concerns is an important source of job stress ( 28 ).…”
Section: Factors Contributing To Workplace Stress In Animal Research mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an inability for those working in research animal facilities to speak openly about their questions and concerns related to animals or research, because of a lack of workplace openness, can lead to workplace stress ( 3 , 27 ). In human health care fields such as nursing, a perceived lack of opportunity to discuss concerns is an important source of job stress ( 28 ).…”
Section: Factors Contributing To Workplace Stress In Animal Research mentioning
confidence: 99%
“…As mentioned, compassion stress is a component of working with animals in science. However, multiple studies have demonstrated that individuals and organizations that incorporate resiliency building into their practices promote both human and animal well-being ( 3 , 4 ). Supporting implementation of the 3Rs (replacement, reduction, and refinement), empowering people to be creative problem solvers, providing opportunities to report questions or concerns, and expecting accountability at all levels, creates a work environment that values people, animals, and science ( 2 ).…”
Section: Tools and Programs To Promote Workplace Well-being In Researmentioning
confidence: 99%
“…Laboratory animal personnel may be at risk for compassion fatigue as a result of their role as animal caretakers that often includes exposure toand sometimes perpetuation of-animal stress and pain. Their compassion fatigue may be exacerbated by the factors discussed above, although relatively few studies have been conducted with laboratory animal personnel specifically (10).…”
Section: Introductionmentioning
confidence: 99%
“…A related concept, empathetic distress fatigue, may better capture the consequences for caregivers such as animal staff 8 . Compassion is an attitude associated with 'feeling for, ' while empathy is more closely associated with a sense of 'feeling with' and has a stronger affective impact 9 .…”
Section: Jordi L Tremoleda and Angela Kertonmentioning
confidence: 99%